A dosimetry technique of high-energy X-ray in MGy range - Rogov, Ju.V.; Shevchenko, V.A.; Shlyakhov, I.N.; Shramenko, B.I.; Tenishev, A.Eh.; Torgovkin, A.V.; Uvarov, V.L.; Zhiglo, V.F. (Вопросы атомной науки и техники, 2015)
Possibility of a dosimetry method for high-energy bremsstrahlung radiation in the range up to МGy and higher by activation of a detector from indium via the ¹¹⁵In (γ,γ') ¹¹⁵mIn reaction with determination of absorbed dose on specific activity of the ¹¹⁵mIn isomer is investigated. To study such an approach, a method based on joint irradiation of a stack of thin targets is offered. Each target includes the foils from indium and molybdenum of natural isotopic composition, and also a standard dosimeter in the form of a plate from PMMA. Preliminary study of indium activation (with due regard to known data on the reaction cross section), detector thermal stability, yield of the reference reactions ⁹²Mo(γ,2n)⁹⁰Mo and ¹⁰⁰Mo(γ,n)⁹⁹Mo as well as absorbed dose in PMMA, was conducted by means of computer simulation. The measurement of specific activity of ¹¹⁵mIn, ⁹⁰Mo and ⁹⁹Mo was carried out jointly with the absorbed dose of in PMMA using the Harwell Red 4034 dosimeters. Sensitivity of the method against end-point energy of X-Ray in the range 8 to 71 MeV has been established. Досліджена можливість дозиметрії високоенергетичного гальмівного випромінювання в діапазоні доз ~МГрей і вище шляхом активації індію за реакцією ¹¹⁵In(γ,γ′)¹¹⁵mIn з визначенням поглинутої дози з питомої активності ізомеру ¹¹⁵mIn. Для дослідження такого підходу запропонована методика, що заснована на сумісному опромінюванні набору тонких мішеней. Кожна мішень включає фольги з індію і молібдену, а також стандартний дозиметр у вигляді пластини з ПММА. Методом моделювання проведено попереднє дослідження активації індію з урахуванням відомих даних з перетину реакції, теплової стійкості детектора, виходу референтних реакцій ⁹²Mo(γ,2n)⁹⁰Mo and ¹⁰⁰Mo(γ,n)⁹⁹Mo у молібдені, а також поглинутої дози в ПММА. Виконано вимірювання питомої активності ¹¹⁵mIn, ⁹⁰Mo and ⁹⁹Mo, а також поглинутої дози гальмівного випромінювання з використанням дозиметрів Harwell Red 4034. Встановлена чутливість методу залежно від граничної енергії гальмівного випромінювання в діапазоні 8…71 МеВ. Исследована возможность дозиметрии высокоэнергетичного тормозного излучения в диапазоне доз ~МГрей и выше путем активации индия по реакции ¹¹⁵In (γ,γ') ¹¹⁵mInс определением поглощенной дозы по удельной активности изомера ¹¹⁵mIn. Для изучения такого подхода предложена методика, основанная на совместном облучении набора тонких мишеней. Каждая мишень включает фольги из индия и молибдена, а также стандартный дозиметр в виде пластины из ПММА. Методом моделирования проведено предварительное исследование активации индия с учетом известных данных по сечению реакции, тепловой стойкости детектора, выхода референтных реакций ⁹²Mo(γ,2n)⁹⁰Mo and ¹⁰⁰Mo(γ,n)⁹⁹Mo в молибдене, а также поглощенной дозы в ПММА. Выполнены измерения удельной активности ¹¹⁵mIn, ⁹⁰Mo and ⁹⁹Mo, а также поглощенной дозы тормозного излучения с использованием дозиметров Harwell Red 4034. Установлена зависимость чувствительности метода от граничной энергии тормозного излучения в диапазоне 8…71 МэВ.